Effect of onion top leaves extract on the quality of smoked Heterotis niloticus (Cuvier, 1829) (Research in Agriculture Livestock and Fisheries, 2018)
Food preservation techniques to improve the oxidative stability of fish-based foods are gaining renewed research interest in natural compounds of vegetable origin as valid alternatives to synthetic preservatives. This study was designed to determine the effect of Onion Top Leaves Extract (OTLE) on the chemical and sensory qualities of smoked Heterotis niloticus using four concentrations (0, 0.25, 0.5 and 0.75% w/w) and three storage periods replicated four times in a Completely Randomized Design (CRD). A total of 48 fresh samples of H. niloticus were treated with the different concentrations of OTLE, sundried for three hours and smoked using a modified portable drum kiln designed in the laboratory. The treated smoked samples were packaged in paper envelopes and stored at room temperature for a period of three weeks. The results indicated that OTLE concentration had significantly affected (P